Pengaruh Proprioceptive Neuromuscular Facilitation terhadap Kekuatan Fungsi Prehension Cylindrical Grip pada Pasien Stroke Non-Hemoragik - Sabirin Berampu; Elsaria Br Sembiring (Jurnal Riset Hesti Medan, 2021)
Stroke is a disease that is most commonly found today, stroke has a high mortality and disability rate. Stroke can cause physical disability in productive age and old age. This study aims to determine the effect of Proprioceptive Neuromuscular Facilitation (PNF) on the strength of the prehension Cylindrical grip function in non-hemorrhagic stroke patients. This research is a quantitative study with a quasi-experimental design, one group pretest and posttest, the samples were taken by purposive sampling, namely non-hemorrhagic stroke patients who visited the physiotherapy poly at Grandmed Lubuk Pakam Hospital. The results showed a p-value of 0.001 which means that there is an effect of PNF on the strength of the prehension Cylindrical grip function in non-hemorrhagic stroke patients.